Dissociable Effects of Reward on P300 and EEG Spectra Under Conditions of High vs. Low Vigilance During a Selective Visual Attention Task - Liu, Jia; Zhang, Chi; Zhu, Yongjie; Liu, Yunmeng; Sun, Hongjin; Ristaniemi, Tapani; Cong, Fengyu; Parviainen, Tiina (Frontiers in Human Neuroscience, 2020)
The influence of motivation on selective visual attention (SVA) in high versus low vigilance is poorly understood. We recorded EEG during prolonged 2 hours 20 min flanker task and explored the effect of vigilance levels and reward on behavioral and neural measures. We demonstrated that prolonged task performance results in vigilance decrement or mental fatigue, impairing behavioral and neural activities. Monetary reward in low vigilance could lead to an improvement in accuracy, reaction time, and omitted responses. The fatigue-related decrease in P300 amplitude recovered to high-vigilance level by manipulating motivation, whereas the fatigue-related increase in P300 latency was not modulated by reward. This suggests that processing capacity, but not timing of processing, is sensitive to motivation. Additionally, the fatigue-related increase in stimulus-induced rhythmic power at 1-4 Hz was sensitive to vigilance decrement and reward. However, the rhythmic power at 4-8 Hz was only impaired by vigilance decrement. These findings suggest mental fatigue impairs behavior and neural performance. After manipulating motivation, only some neural underpinnings of SVA were recovered from fatigue impairment. These results further indicate dissociable neural mechanisms underlying fatigue-related decrease vs. reward-related increase in attentional resources.